SIFAT FISIKOKIMIA DAN SENSORIS BERAS ANALOG JAGUNG DENGAN PENAMBAHAN TEPUNG KEDELAI - Tyas Hermala Anindita; Feri Kusnandar; Slamet Budijanto (Jurnal Teknologi dan Industri Pangan, 2020)
Rice analogs are rice-like products processed from various non-rice carbohydrate sources, such as corn flour. A high-protein rice analog can be produced with the addition of soybean into the formula of corn-based rice analog. This research aimed to evaluate a high-protein rice analogs made with the addition of soybeans (Grobogan or Detam-1 variety) in terms of their chemical composition, water holding capacity, texture and sensory qualities. The rice analogs were produced from corn flour, soybean flour, sagoo starch, glycerol monostearate (GMS) and water using hot-extrusion methods. The percentage of Grobogan or Detam-1 soybean flour added varied, i.e. 10, 15, 20, and 25%. The addition of soybean flour of Grobogan variety increased the protein content of the rice analog. A high-protein rice analog can be obtained by adding 20% Grobogan soybean flour or 15% Detam-1 soybean flour. The fat and dietary fiber content of rice analog also increased, while the carbohydrate content decreased. The hardness and cohesiveness of the rice analog decreased as the amount of soybean flour addition increased. However, panelists did not detect any changes up to 25% of soybean flour addition. The water holding capacity of the rice analog also decreased as the amount of soybean flour increased. The panelists detected the changes in water holding capacity starting from 20% soybean flour addition.